Studying Network Mechanisms Using Intracranial Stimulation in Epileptic Patients - David, Olivier; Bastin, Julien; Chabardès, Stéphan; Minotti, Lorella; Kahane, Philippe (Frontiers in Systems Neuroscience, 2010)
Patients suffering from focal drug-resistant epilepsy who are explored using intracranial electrodes allow to obtain data of exceptional value for studying brain dynamics in correlation with pathophysiological and cognitive processes. Direct electrical stimulation (DES) of cortical regions and axonal tracts in those patients elicits a number of very specific perceptual or behavioural responses, but also abnormal responses due to specific configurations of epileptic networks. Here, we review how anatomo-functional brain connectivity and epilepsy network mechanisms can be assessed from DES responses measured in patients. After a brief summary of mechanisms of action of brain electrical stimulation, we recall the conceptual framework for interpreting DES results in the context of brain connectivity and review how DES can be used for the characterisation of functional networks, the identification of the seizure onset zone, the study of brain plasticity mechanisms, and the anticipation of epileptic seizures. This pool of exceptional data may be underexploited by fundamental research on brain connectivity and leaves much to be learned.